Strategi Inklusif untuk Menjembatani Kesenjangan Digital: Studi Kasus 9 Provinsi Kepulauan di Indonesia - Herie Saksono (Research and Development Agency Ministry of Home Affairs, 2024)
As the world’s largest archipelagic country, Indonesia faces unique challenges in digital transformation, particularly regarding digital disparities across its nine archipelagic provinces. This study explores how Indonesia’s archipelagic characteristics can be leveraged to bridge digital gaps and achieve inclusive digital transformation. Using a qualitative-exploratory approach with thematic analysis of secondary data, the research develops an archipelagic-based digital transformation framework. The findings reveal that infrastructure limitations, low digital literacy, and fragmented geography drive significant digital disparities. The “Hub and Spoke” model effectively addresses these challenges, with well-connected digital hubs serving as knowledge and support centers for surrounding islands. The research findings indicate that an archipelago-based approach, combining top-down and bottom-up elements, is most effective for implementing digital transformation. In conclusion, successful digital transformation in Indonesia requires a strategy that considers the geographic characteristics of the archipelago, supported by comprehensive government policies, adequate infrastructure, and multi-stakeholder collaboration. Key recommendations include increasing investment in telecommunications infrastructure in the 3T (frontier and remote) regions, developing digital literacy based on local characteristics, and strengthening dodeca-helix partnerships for sustainable digital transformation implementation.